A Membrane-proximal Tetracysteine Motif Contributes to Assembly of CD3δε and CD3γε Dimers with the T Cell Receptor() - Xu, Chenqi (J Biol Chem, 2006)
Assembly of the T cell receptor (TCR) with its dimeric signaling modules, CD3δε, CD3γε, and ζζ, is organized by transmembrane (TM) interactions. Each of the three assembly steps requires formation of a three-helix interface involving one particular basic TCR TM residue and two acidic TM residues of the respective signaling dimer. The extracellular domains of CD3δε and CD3γε contribute to assembly, but TCR interaction sites on CD3 dimers have not been defined. The structures of the extra-cellular domains of CD3δε and CD3γε demonstrated parallel β-strands ending at the first cysteine in the CXXCXEXXX motif present in the stalk segment of each CD3 chain. Mutation of the membrane-proximal cysteines impaired assembly of either CD3 dimer with TCR, and little complex was isolated when all four membrane-proximal cysteines were mutated to alanine. These mutations had, however, no discernable effect on CD3δε or CD3γε dimerization. CD3δε assembled with a TCRα mutant that lacked both immunoglobulin domains, but shortening of the TCRα connecting peptide reduced assembly, consistent with membrane-proximal TCRα-CD3δε interactions. Chelation of divalent cations did not affect assembly, indicating that coordination of a cation by the tetracysteine motif was not required. The membrane-proximal cysteines were within close proximity but only formed covalent CD3 dimers when one cys-teine was mutated. The four cysteines may thus form two intra-chain disulfide bonds integral to the secondary structure of CD3 stalk regions. The three-chain interaction theme first established for the TM domains thus extends into the membrane-proximal domains of TCRα-CD3δε and TCRβ-CD3γε.